Acute peritonitis in geriatrics - Arriaga, Pedro (Cirugía del Uruguay, 1975)
Seven cases of acute peritonitis in geriatric patients are discussed, laying a special stress in the clinical, diagnostic and therapeutic features. The authors remark the usual scarcity of signs and symptoms of these cases and the diagnostic difficulties, related to the. multiple pathology which is frequently present. General therapeutic trends ar established.